E5M7+ (E=C–Pb, M=Li–Cs): A Source of Viable Star‐Shaped Clusters - Vásquez‐Espinal, Alejandro; Palacio‐Rodríguez, Karen; Ravell, Estefanía; Orozco‐Ic, Mesías; Barroso, Jorge; Pan, Sudip; Tiznado, William; Merino, Gabriel (Chemistry, an Asian journal, 2018)
Herein we report the systematic exploration of the potential energy surfaces of a series of clusters with formula E5M7+ (E=C‐Pb and M=Li‐Cs). Fifteen of these combinations adopt a D5h three‐dimensional seven‐pointed star‐like structure in a singlet state, where M atoms interact electrostatically with the E5 ring. The determining factors in the relative preference of having the D5h structure over the most competitive isomer or vice‐versa are analyzed. These star‐shaped systems satisfy the 4n+2 Hückel's rule and exhibit a strong diatropic (σ and π) response to an external magnetic field. Aiming for the stars: A systematic exploration of the potential energy surface of twenty‐five combinations with formula E5M7+ (E=C–Pb, M=Li–Cs) was conducted. Fifteen of these combinations adopt a D5h star‐like shape with five equatorial and two axial M atoms. These systems exhibit π electronic delocalization and a diatropic response under an external magnetic field.